Histoplasmosis as a late infectious complication following heart transplantation in a patient with Chagas' disease - Bacal,Fernando (2001)
Infectious complications following heart transplantation are an important cause of morbidity and mortality. Generally, bacterial infections are predominant; however, fungal infections can be responsible for up to 25% of infectious events. We report the case of a patient who presented with histoplasmosis as an infectious complication five years after heart transplantation due to a chagasic cardiopathy. This association has rarely been reported in the international literature.